2020
DOI: 10.2166/wst.2020.252
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fe2O3/ZrO2 loaded polyhedron ball on photocatalytic degradation of diesel pollutants in seawater under visible light

Abstract: Fe2O3/ZrO2 nanocomposite photocatalyst was successfully prepared by coprecipitation method for the degradation of diesel pollutants in seawater under visible light. The effects of doping ratio, calcination temperature, photocatalyst dosage, initial diesel concentration, H2O2 concentration, and reaction time on the photocatalytic removal efficiency were investigated. Moreover, the optimal conditions for Fe2O3/ZrO2 nanocomposite photocatalyst to degrade marine diesel pollution were determined. The removal effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The degradation efficiency of methylene blue (MB) under visible light using BiVO 4 /Fe 3 O 4 within 5 h was higher (92%) compared with that of the pure BiVO 4 catalyst (72.5%). Wang et al (2020) found that Fe 2 O 3 /ZrO nanocomposite exhibited better light absorption capacity than the individual catalysts. Wang (Wang et al (2021) synthesized a three‐dimensional BiOI/g‐C 3 N 4 catalyst through a distribution synthesis method for the degradation of tetrachloroethylene (TCH) and 2,6‐dichlorophenol (2,6‐DCP) under visible light irradiation.…”
Section: Review On Photocatalytic Degradation Of Water Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation efficiency of methylene blue (MB) under visible light using BiVO 4 /Fe 3 O 4 within 5 h was higher (92%) compared with that of the pure BiVO 4 catalyst (72.5%). Wang et al (2020) found that Fe 2 O 3 /ZrO nanocomposite exhibited better light absorption capacity than the individual catalysts. Wang (Wang et al (2021) synthesized a three‐dimensional BiOI/g‐C 3 N 4 catalyst through a distribution synthesis method for the degradation of tetrachloroethylene (TCH) and 2,6‐dichlorophenol (2,6‐DCP) under visible light irradiation.…”
Section: Review On Photocatalytic Degradation Of Water Pollutantsmentioning
confidence: 99%
“…synthesized a magnetic separation visible light photocatalyst BiVO 4 /Fe 3 O 4 through ultrasonication. The degradation efficiency of methylene blue (MB) under visible light using BiVO 4 /Fe 3 O 4 within 5 h was higher (92%) compared with that of the pure BiVO 4 catalyst (72.5%) Wang et al (2020). found that Fe 2 O 3 /ZrO nanocomposite exhibited better light absorption capacity than the individual catalysts.…”
mentioning
confidence: 96%
“…In addition, the photoactive sites used to remove OTC-HCl increased after modification. Excessive catalyst could diffuse reflection of light in the reaction system, thereby affected the use of light by the photocatalyst and reduced the removal rate of OTC-HCl(Wang et al, 2020a).…”
mentioning
confidence: 99%